2003
DOI: 10.1046/j.1365-2958.2003.03311.x
|View full text |Cite
|
Sign up to set email alerts
|

The product of the UTH1 gene, required for Bax‐induced cell death in yeast, is involved in the response to rapamycin

Abstract: SummaryA yeast mutant was isolated that was resistant to Baxinduced cell death. It supports a mutation leading to decreased amounts of the protein Uth1p. A strain in which the UTH1 gene is disrupted also exhibits resistance to Bax expression. The absence of Uth1p does not change the mitochondrial localization of Bax, its insertion in the mitochondrial outer membrane or its cytochrome c -releasing activity. On the other hand, the absence of Uth1p does prevent the appearance of other hallmarks related to Bax exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
85
0
4

Year Published

2003
2003
2009
2009

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(93 citation statements)
references
References 55 publications
4
85
0
4
Order By: Relevance
“…25 However, accumulation of ubiquitin-conjugated proapoptotic proteins did not give rise to a higher incidence of apoptotic cell death. There is a possibility that certain proapoptotic proteins have a function in apoptosis and autophagic cell death, as proposed recently for Bax by Camougrand et al 29 Interestingly, the core protein machinery necessary to drive formation of autophagosomes includes a ubiquitin-like protein conjugation system. 16,22 Moreover, Kostin et al 8 reported that autophagic vacuoles are positive for ubiquitin immunolabeling.…”
Section: Discussionmentioning
confidence: 99%
“…25 However, accumulation of ubiquitin-conjugated proapoptotic proteins did not give rise to a higher incidence of apoptotic cell death. There is a possibility that certain proapoptotic proteins have a function in apoptosis and autophagic cell death, as proposed recently for Bax by Camougrand et al 29 Interestingly, the core protein machinery necessary to drive formation of autophagosomes includes a ubiquitin-like protein conjugation system. 16,22 Moreover, Kostin et al 8 reported that autophagic vacuoles are positive for ubiquitin immunolabeling.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Uth1 mutants survive and proliferate when expressing the human proapoptotic cell death gene bax. 47 The totality of these findings suggests that Uth1p may provide a direct association between mitophagy and cell death.…”
Section: Autophagy In Cell Deathmentioning
confidence: 99%
“…UTH1, a gene that is possibly involved in autophagic death, is needed for efficient Baxmediated killing in yeast [74]. While deletion of UTH1 does not prevent the insertion of Bax into the mitochondrial outer membrane or cytochrome c release, it inhibits the appearance of mitochondrial lipid oxidation and ROS production [74], suggesting an additional cytochrome c independent but autophagy-related pathway of Bax triggering cell death. Furthermore, UTH1 is involved in various types of stress response and ageing [75,76] and its deletion confers resistance to rapamycin [74].…”
Section: Mitochondria and Autophagy In Bax-induced Cell Deathmentioning
confidence: 99%